High Densities of Tumor-Associated Plasma Cells Predict Improved Prognosis in Triple Negative Breast Cancer - Yeong, Joe; Lim, Jeffrey Chun Tatt; Lee, Bernett; Li, Huihua; Chia, Noel; Ong, Clara Chong Hui; Lye, Weng Kit; Putti, Thomas Choudary; Dent, Rebecca; Lim, Elaine; Thike, Aye Aye; Tan, Puay Hoon; et al. (Frontiers in Immunology, 2018)
Breast cancer is the most common malignancy affecting women, but the heterogeneity of the condition is a significant obstacles to effective treatment. Triple negative breast cancers (TNBCs) do not express HER2 or the receptors for estrogen or progesterone, and so often have a poor prognosis. Tumor-infiltrating T cells have been well-characterized in TNBC, and increased numbers are associated with better outcomes; however the potential roles of B cells and plasma cells have been largely-overlooked. Here we conducted a retrospective correlative study on the expression of B cell/plasma cell-related genes, and the abundance and localization of B cells and plasma cells within TNBCs, and clinical outcome. We analyzed 269 TNBC samples and used immunohistochemistry to quantify tumor-infiltrating B cells and plasma cells, coupled with NanoString measurement of expression of immunoglobulin meta-genes. Multivariate analysis revealed that patients bearing TNBCs with above-median densities of CD38+ plasma cells had significantly better disease-free survival (DFS) (HR=0.44; 95% CI 0.26-0.77; p=0.004) but not overall survival, after adjusting for the effects of known prognostic factors. In contrast, TNBCs with higher immunoglobulin gene expression exhibited improved prognosis (OS p=0.029 and DFS p=0.005). The presence of B cells and plasma cells was positively correlated (p<0.0001, R=0.558), while immunoglobulin gene IGKC, IGHM and IGHG1 mRNA expression correlated specifically with the density of CD38+ plasma cells (IGKC p<0.0001, R=0.647; IGHM p<0.0001, R=0.580; IGHG1 p< 0.0001, R=0.655). Interestingly, after adjusting the multivariate analysis for the effect of intratumoral CD38+ plasma cell density, the expression levels of all three genes lost significant prognostic value, suggesting a biologically important role of plasma cells. Last but not least, the addition of intratumoral CD38+ plasma cell density to clinicopathological features significantly increased the prognostic value for both DFS (∆LRχ2=17.28, p=1.71E-08) and OS (∆LRχ2=10.03, p=6.32E-08), compared to clinicopathological features alone. The best combination was achieved by integrating intratumoral CD38+ plasma cell density and IGHG1 which conferred the best added prognostic value for DFS (∆LRχ2=27.38, p=5.22E-10) and OS (∆LRχ2=21.29, p=1.03E-08). Our results demonstrate that the role of plasma cells in TNBC warrants further study to elucidate the relationship between their infiltration of tumors and disease recurrence.